Strength of Geopolymer Cement Curing at Ambient Temperature by Non-Oven Curing Approaches: An Overview - Pitiwat Wattanachai (2018)
© Published under licence by IOP Publishing Ltd. At the present day, a concept of environmentally friendly construction materials has been intensively studying to reduce the amount of releasing greenhouse gases. Geopolymer is one of the cementitious binders which can be produced by utilising pozzolanic wastes (e.g. fly ash or furnace slag) and also receiving much more attention as a low-CO2 emission material. However, to achieve excellent mechanical properties, heat curing process is needed to apply to geopolymer cement in a range of temperature around 40 to 90°C. To consume less oven-curing energy and be more convenience in practical work, the study on geopolymer curing at ambient temperature (around 20 to 25°C) is therefore widely investigated. In this paper, a core review of factors and approaches for non-oven curing geopolymer has been summarised. The performance, in term of strength, of each non-oven curing method, is also presented and analysed. The main aim of this review paper is to gather the latest study of ambient temperature curing geopolymer and to enlarge a feasibility of non-oven curing geopolymer development. Also, to extend the directions of research work, some approaches or techniques can be combined or applied to the specific properties for in-field applications and embankment stabilization by using soil-cement column.